On the Category of Weakly Laskerian Cofinite Modules - Bahmanpour, Kamal (MATHEMATICA SCANDINAVICA, 2014)
Let R denote a commutative Noetherian (not necessarily local) ring and I be an ideal of R. The main purpose of this note is to show that the category WL(R, I)_cof of I-cofinite weakly Laskerian R-modules forms an Abelian subcategory of the category of all R-modules.